Transdisciplinarity in extended reality (XR) research design: Technological transformation and social good (co-creation session at XR + Creativity Symposium, University of Newcastle, 2020). Issue 1 (1st June 2021) - Orr, Nikolas; Matthews, Benjamin; See, Zi Siang; Burrell, Andrew; Day, Jamin; Seengal, Divya
This article collates and synthesizes the discussion results of a collaborative research exercise, known as a 'co-creation session', formed of a multi-disciplinary group of extended reality (XR) researchers and practitioners. The session sought to develop and theorize the concept of 'transformative technologies for good' in creative, applied and clinical contexts. Notions of 'cutting-edge' practice were visited from a critical standpoint; participants established that innovation, when measured in terms of social good, challenges technological and economic paradigms of progress. Conversation between participants centred on four key areas: skills and knowledge for effective XR research, appropriate methods and sites for diffusion of XR research, the future of the field, and the possible contributions of XR and associated research to problems arising from COVID-19. The session offered further insights into research design related to composition of participant groups in terms of disciplinary knowledge, activity design, and remote digital interfaces.